ANALISIS PENGARUH PERBEDAAN SURFACE PREPARATION DENGAN VARIASI JENIS CAT TERHADAP KEKUATAN ADHESI DAN KETAHANAN IMPACT COATING PADA BAJA SS400 - Sativa , Zahra; Manik , Parlindungan Manik; Mursid , Ocid (Jurnal Rekayasa Mesin, 2024)
Surface preparation is a fundamental thing that must be done before applying the coating to the material. A good painting will be obtained with good surface preparation treatment. This research aims to determine the effect of different surface preparation methods and various types of paint on adhesion strength and impact coating resistance. The type of material used in this research is SS400 steel with three different surface preparation methods, namely sandblasting, power tools, and hand tools following ISO 8501-1 standards, and with a variety of three different types of paint, namely epoxy, polyurethane, and alkyd paint. Adhesion strength testing uses the pull-off test method and impact resistance testing is carried out using the impact coating test. This test is carried out after the coating has been applied and the paint has dried completely. The results of the tests that have been carried out show that the highest average adhesion value of the three surface preparation methods carried out is obtained from polyurethane coatings. The best coating durability test results were obtained by polyurethane paint with only cracks occurring using the hand tool method at a height of 0.6 m. The conclusion obtained is that the best type of coating in this research is polyurethane coating and the best method is cleaning using the sandblasting method.